DNA Barcoding and CITES-Listed Wedgefish (Rhynchobatidae, Rhinidae) from South Bangka, Indonesia - Siti Aisyah; Novi Santia; Okto Supratman; Ahmad Fahrul Syarif; Anggraeni Anggraeni; Okto Supratman (Universitas Diponegoro, 2021)
Overfishing of wedgefish greatly affects its population and the balance of the marine ecosystem. This is exacerbated by their relatively low fecundity, slow growth, and late maturity results in one of the lowest population growth rate within elasmobranch species. However, lacking database information results in insufficient regulations and surveillance of wedgefish fishing. The current situation is feared to the risk of wedgefish’s survival, especially in Bangka Belitung Islands, Indonesia. Fundamental to a database is the accurate identification of wedgefish species based on mitochondrial DNA (mtDNA) analysis. This study aimed to use DNA barcodes to identify, determine the conservation status, and the status according to the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). We collected samples including unidentified fin samples from confiscated illegal fishing catches, the traditional markets and fishing docks, South Bangka. In this research, we used DNA Barcoding (mitocondrial DNA, COI gene) to identify and examine of wedgefish samples. The tissue samples used in this study were identified as species listed in CITES Appendix II, they are Rhynchobatus australiae, Rhynchobatus springeri and Rhina ancylostoma. According to the IUCN Red List, 100% of the wedgefish species found are Critical Endangered at the global level.